Identification and Characterization of vanB2 Glycopeptide Resistance Elements in Enterococci Isolated in Scotland - McGregor, K. F. (American Society for Microbiology, 2000)
Thirty-two vanB glycopeptide-resistant enterococci (28 Enterococcus faecium and 4 Enterococcus faecalis) were collected from hospitalized patients in Glasgow, Edinburgh, Dundee, and Aberdeen, Scotland, and the vanB element in each was compared to vanB1 of E. faecalis strain ATCC 51299. HhaI digestion of PCR fragments of the vanB ligase gene was used to identify vanB subtypes. All E. faecium isolates were vanB2, and all E. faecalis isolates were vanB1. Restriction fragment length polymorphism analysis of a 5,180-bp vanS(B)-vanX(B) long-PCR fragment of the vanB cluster showed the loss of HaeII restriction sites in vanS(B), vanW, and vanX(B) in strains containing a vanB2 ligase gene. Partial sequences of genes in the vanB2 cluster for two genomically distinct Scottish isolates were >99.8% identical to each other. vanS(B2), vanX(B2), and vanB2 sequences differed at the nucleotide level from those of vanS(B), vanX(B), and vanB by 4.2, 4.6, and 4.8%, respectively. The vanB2 resistance element appears to be widespread among VanB glycopeptide-resistant E. faecium strains isolated in Scottish hospitals.